If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -8x = 124 + -29x Solving 13 + -8x = 124 + -29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29x' to each side of the equation. 13 + -8x + 29x = 124 + -29x + 29x Combine like terms: -8x + 29x = 21x 13 + 21x = 124 + -29x + 29x Combine like terms: -29x + 29x = 0 13 + 21x = 124 + 0 13 + 21x = 124 Add '-13' to each side of the equation. 13 + -13 + 21x = 124 + -13 Combine like terms: 13 + -13 = 0 0 + 21x = 124 + -13 21x = 124 + -13 Combine like terms: 124 + -13 = 111 21x = 111 Divide each side by '21'. x = 5.285714286 Simplifying x = 5.285714286
| 2x^2-2x+6=0 | | 28a+14=15a-7 | | 4x-1/2=5x | | 0.60X+0.5(10-X)=.10(-39) | | 5-n=-8n | | -2z+8=21+4z | | x-1*x-1= | | y-1=2y-1 | | 12z+6=z-1 | | 8x-40=20x-4 | | 6x+5.5=x+11 | | -17=10u | | 124-7x=11x+18 | | 287-4x=41x+22 | | 6-9x=47-16x | | -x^4+x^3+6x^2-14x+12=0 | | -x^5+3x^4+4x^3-26x^2+40x-24=0 | | m^3+2m-15=0 | | 5x+1=14x-82 | | 8x+4=16-9x | | (x-6)(2x+3)=0 | | 4x^2+22x=-16 | | 8x-12=52 | | 2x+6=x+19 | | 9x-23=58 | | 24x^4-54x=12x^3-27x | | 24x^4-54x^2-12x^3+27x=0 | | 156-3x=6x+21 | | 35-3c=6c+3.5 | | 12-2h=14h-36 | | 107-5x=22x+20 | | 8g-9=5g+12 |